Desain Sistem Informasi Perpustakaan Desa Dalam Rangka Mendukung Program Transformasi Perpustakaan Berbasis Inklusi Sosial - Eka Wardhani Suprihatin (Perpustakaan Nasional, 2021)
The village library as a provider of reading material facilities closest to the community is very important, but its existence has not received serious attention. Therefore the National Library of Indonesia has a Social Inclusion-Based Library Transformation program which will provide a new understanding of the existence of village libraries, so that they are better known by the community and can be used properly. For this reason, it is necessary to design a village library information system so that the existence of the library is well organized in accordance with the standards set by the National Library of Indonesia. The analytical method used is descriptive qualitative with a literature study approach, this article provides an overview of the current condition of village libraries that still use conventional library concepts and an overview of library information designs that run social inclusion-based library programs. Social inclusion-based village libraries do not provide loan services and help books, but also provide ICT-based community activities. From the research, it can be concluded that: 1.) the rural library information system design is important to be developed, so that the library is able to fulfill people’s need; 2.) the rural library information system design is important to be developed to be able to give enough facilities for the variations of people empowerment using the library collections; 3.) the implementation of ICT (Information and Communication Technology) in the library is more directed in the promotion and documentation activities to promote the literation development and library activities.